Cardiac metastasis: a rare involvement of primitive neuroectodermal tumour of the lung - Ngow, Harris Abdullah; Wan Khairina, Wan Mohd Nowalid (Springer Netherlands, 2011)
A 15 year-old adolescent was referred with 2 month history of worsening of breathlessness and haemoptysis. He also reported constitutional symptoms of fever, poor appetite and weight loss. The chest roentgenogram showed a massive right pleural effusion with apparent cardiomegaly. The cardiac silhouette over the right heart border was obliterated and the mediastinum was widened. Computed tomogram of the thorax showed a bulky heterogeneous mass in the right lung with extension to the heart. Subsequent CT guided lung biopsy revealed Primitive Neuroectodermal tumour (PNET). Here, we illustrate the clinical course of an aggressive pulmonary PNET with lethal cardiac metastasis.